The influence of neuroscience on the execution of criminal sentence, from the purpose to reincorporation (2020)
The social reintegration is one of the ends of the penalty that has been causing the greatest concern in the doctrine, the criminal policy and the society in general, during the last years; The ineffectiveness of the programs being carried out in the current prison system entails to the continued recurrence of crime. that prisons become not centers of re- socialization but specialized schools of crime. For this reason, in this article we intend to reflect on the influence that neurosciences could have on the prison system with regard to the execution of the sentence from the resocializing goal; This, taking into account its advantages and disadvantages.